JAVANESE LANGUAGE ATTITUDE TOWARDS SPEECH LEVELS OF VERNACULAR IN DISTRICT OF BANDAR SELAMAT MEDAN - Farida Romaito Pohan; Ranta Butarbutar (Musamus Journal of Language and Literature, 2020)
The purpose of this study was to determine the attitude of Javanese language through speech level in District of Bandar Selamat, Medan. The method used in this research is qualitative research. The results showed that (1) there were two types of speech levels in District of Bandar Selamat, namely Madya and Ngoko. They use the Intermediate speech level not because they know about the speech level well, but such speaking style comes naturally to themselves because of the influence of family and environment and they still maintain and care about manners, Andap-ansor, and Tanggap ing sasmita even though they live in another city. And they use Ngoko's speech level because of the transmigration effect that requires them to use Indonesian because they are in an environment that consists of many tribes, therefore they speak the same as the people there and don't care anymore with manners, Andap-ansor and Tanggap ing sasmita ( 2) Javanese language character and attitude in District of Bandar Selamat, they have high loyalty to their local language, they are proud to use their local language and their awareness of norms is very weak because they live on the island of Sumatra so the norms that exist in Javanese people are not very important (3) Javanese in Bandar Selamat have a positive attitude towards their local language because they still care about etiquette, Andap-ansor and Tanggap ing sasmita as do the Javanese on the island of Java.